Revisiting the Legality of Underage Marriage in the Views of Islamic Legal Scholars - Abidin, Zainal; Ja'far, Ja'far; Khalil, Munawar; Iqbal, Muhammad (Sekolah Tinggi Agama Islam Sumatera Medan, 2024)
Child marriage has often been one of the most heated debates amongst Islamic jurisprudents (‘fuqahâ’) and is even opposed by various groups for a variety of reasons, including legislative regulations, health, social and economic concerns, and children’s rights. This article examines the legality of underage marriage according to Islamic law scholars. This research is a library-based study using a conceptual and comparative approach. The data sources for this research include the prominent fiqh texts of the Mâlikî, Hanafî, Shâfi‘î, Hanbalî, and Shia Imamiyya schools. The data is analyzed using content analysis methodology. The findings of this study indicate that the four Sunni schools and the Shia Imamiyya school recognize the permissibility of child marriage, with various conditions, particularly regarding the guardian (wali) who performs the marriage and the potential benefits or harms of the marriage. This study complements research on the perspectives of the five major fiqh schools regarding the legality of child marriage. It also provides an alternative perspective for interpreting the legal regulations on marriage in Indonesia.